A UK hospital survey to explore healthcare professional views and attitudes to patients incorrectly labelled as penicillin allergic: an antibiotic stewardship patient safety project. Issue 6 (24th May 2018) - Wilcock, Michael; Powell, Neil; Sandoe, Jonathan
Abstract : Objectives: To ascertain the views, beliefs and attitudes of hospital staff to incorrect penicillin allergy records in order to determine healthcare worker motivation for the implementation of a penicillin de-labelling antibiotic stewardship intervention at the study hospital. Methods: An electronic questionnaire (SurveyMonkey) was distributed to medical, nursing and pharmacy staff at a 750-bed teaching district general hospital with no specialist allergy service. Results: 193 staff responded (58% medical, 31% nursing and 11% pharmacy). Virtually all staff had encountered patients who believed themselves to be penicillin allergic, but felt the patient's belief to be erroneous. The potential negative consequences of an incorrectly assigned penicillin allergy label were acknowledged by the majority of respondents. In total, 188/190 (99%) of staff thought patients having an incorrect allergy status to penicillin was a problem and required a solution. Staff reported they would feel confident using a validated evidence-based question tool to de-label patients incorrectly labelled as penicillin allergic if the process was supported by Trust management, although many still felt apprehensive about de-labelling patients for fear of patient harm through inappropriate de-labelling. Conclusions: A penicillin allergy de-labelling intervention would be well supported by healthcare workers at the study hospital, demonstrating a receptive environment for this behavioural change intervention. Further exploration of the barriers and levers to introducing an intervention is required using behavioural change methodology in order to design a successful de-labelling intervention.